Constitutional and Legal Regulation of State Authority Interaction on Citizen Appeals: Foreign Experience - V. Markhgeym, Marina; G. Mikhaleva, Galia; E. Novikova, Alevtina; A. Klyagina, Dar'ya; Georgiev Sivkov, Tsvetan (International Journal of Criminology and Sociology, 2022)
The purpose of this article is to identify the foreign experience of constitutional legalization of the basic foundations of interaction between government bodies regarding citizens' appeals. The study was built based on a dialectical approach to the disclosure of legal phenomena and processes using general scientific (systemic, logical, analysis and synthesis) and private scientific methods. The claimed interaction becomes relevant in modern conditions because that there is the coordination of the interests between an individual and the state in this process that is demanded to strengthen democratic values. Systematization of foreign constitutional experience, which appears in the comparative legal aspect as part of the general human rights theory.